Therapeutic effect of natural polyphenols against glioblastoma - Beylerli, Ozal; Beilerli, Aferin; Shumadalova, Alina; Wang, Xiaoxiong; Yang, Mingchun; Sun, Hanran; Teng, Lei (Frontiers in Cell and Developmental Biology, 2022)
Glioblastoma (GBM) is the most common and aggressive tumor of the central nervous system, which has a highly invasive growth pattern, which creates poor prospects for patient survival. Chemotherapy and tumor surgery are limited by anticancer drug resistance and tumor invasion. Evidence suggests that combinations of treatments may be more effective than single drugs alone. Natural polyphenolic compounds have potential as drugs for the treatment of glioblastoma and are considered as potential anticancer drugs. Although these beneficial effects are promising, the efficacy of natural polyphenolic compounds in GBM is limited by their bioavailability and blood-brain barrier permeability. Many of them have a significant effect on reducing the progression of glioblastoma through mechanisms such as reduced migration and cell invasion or chemosensitization. Various chemical formulations have been proposed to improve their pharmacological properties. This review summarizes natural polyphenolic compounds and their physiological effects in glioblastoma models by modulating signaling pathways involved in angiogenesis, apoptosis, chemoresistance, and cell invasion. Polyphenolic compounds are emerging as promising agents for combating the progression of glioblastoma. However, clinical trials are still needed to confirm the properties of these compounds in vitro and in vivo.